1980
DOI: 10.1002/aic.690260608
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical modeling of catalytic converter lightoff: Single‐pellet studies

Abstract: A detailed mathematical model of a single catalyst pellet has been developed to describe its behavior under transient conditions encountered during the warmup period of automobile exhaust catalytic converters. In contrast to the converter models previously reported in the literature, this model is capable of describing the time-dependent behavior of a composite catalyst pellet, and thus provides a convenient means of examining the effects of poison penetration and various noble metal impregnation strategies in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

1983
1983
2008
2008

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 20 publications
2
29
0
Order By: Relevance
“…In accord with the results of our previous study (Oh et al, 1980), however, the converter lightoff times (say, the time required for 50% conversion) for CO, C3H6, and Hz were predicted to be very similar because of the kinetic coupling between the species. (In all cases considered, the predicted conversion of methane was negligibly small.)…”
Section: Analysis Of Converter Waryup Behaviorsupporting
confidence: 88%
See 3 more Smart Citations
“…In accord with the results of our previous study (Oh et al, 1980), however, the converter lightoff times (say, the time required for 50% conversion) for CO, C3H6, and Hz were predicted to be very similar because of the kinetic coupling between the species. (In all cases considered, the predicted conversion of methane was negligibly small.)…”
Section: Analysis Of Converter Waryup Behaviorsupporting
confidence: 88%
“…11, because the validity of this uniform pellet temperature assumption in converter warmup studies has been demonstrated previously (Oh et al, 1980). It is important to emphasize that Eqs.…”
Section: Basic Equationsmentioning
confidence: 73%
See 2 more Smart Citations
“…Chemical reaction kinetics is a key aspect in the modelling of catalyst performance. Models of reaction kinetics for catalytic converters may be divided into two categories: (1) Langmuir-Hinshelwood type with few global reaction steps [2,3,4], (2) detailed catalytic surface reaction mechanism [5,6,7].…”
Section: Introductionmentioning
confidence: 99%